Lubricant additive and lubricant composition
By using polymer additives with specific structural units in lubricating oil, the problem that existing friction reducing agents cannot effectively reduce friction under certain conditions is solved, and better lubrication effect and equipment life are achieved.
Patent Information
- Application Number
- JP2024162514
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-28
- Filing Date
- 2024-09-19
- Publication Date
- 2025-04-09
AI Technical Summary
The friction reducing agent used in the prior art in lubricating oil cannot effectively reduce friction under certain conditions, resulting in a shortened equipment life and an increased energy consumption.
A lubricating oil additive is used, made of a polymer having structural units from a radiopolymerizable unit, wherein at least two adjacent carbon atoms each carry one hydroxyl group and contain 0.001 to 3.70 mmol/g of hydroxyl groups in the polymer.
This additive significantly improves the friction reduction effect of lubricant oil, extends equipment life, and reduces energy consumption.
Smart Images

Figure 2025058959000001 
Figure 2025058959000002 
Figure 2025058959000003
Abstract
Description
[Technical field]
[0001] The present invention relates to additives for use in lubricating oils and lubricating oil compositions. [Background technology]
[0002] Lubricating oil compositions, such as engine oils and driveline oils for automobiles, are composed of base oils and a number of additives. Friction reducers, a type of additive, reduce friction, thereby reducing energy loss and preventing seizure, thereby extending the life of equipment. In recent years, the viscosity of lubricating oils has been reduced in order to improve fuel efficiency, and as a result, the load on the contact surfaces between metals has become more severe, making the role of friction reducers even more important.
[0003] Examples of friction reducers include oiliness improvers such as long-chain fatty acid esters and fatty acid amides, anti-wear agents such as phosphate esters and zinc dithiophosphates, extreme pressure agents such as organic sulfur compounds and organic halogen compounds, and friction modifiers such as organic molybdenum compounds. However, depending on the conditions and environment of use, there is a problem that the friction reduction effect is insufficient with these additives alone. In order to overcome this problem, studies are being conducted on the use of polymer materials as friction reducers. For example, Patent Document 1 discloses that a copolymer having an alkyl acrylate and a hydroxyalkyl acrylate as constituent monomers is effective as a friction and wear reducer for lubricating oils. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2013-124266 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, the friction and wear reducer for lubricating oils of Patent Document 1 is insufficient in reducing friction. A primary object of the present invention is to provide a lubricating oil additive and a lubricating oil composition which are excellent in friction reducing effect. [Means for solving the problem]
[0006] The present invention includes the following configurations. [1] A lubricating oil additive comprising a polymer (A) that contains a structural unit derived from a radically polymerizable monomer (a) having a structure in which a hydroxyl group is bonded to each of at least two adjacent carbon atoms, and in which the content of the hydroxyl groups is 0.001 to 3.70 mmol / g. [2] The lubricating oil additive according to [1], wherein the radical polymerizable monomer (a) contains at least one of a monomer represented by the following formula (1) and a monomer represented by the following formula (2): [ka] (In the formula, R 1 is a hydrogen atom or a methyl group, R 2 ~R 4 each independently represents a hydrogen atom or a hydroxyl group, and x represents an integer of 0 to 3. [ka] (In the formula, R 5 is a hydrogen atom or a methyl group, R 6 is an NH or oxygen atom, R 7 is an alkylene group having 1 to 5 carbon atoms or an alkylene group having 1 to 5 carbon atoms and a hydroxyl group; R 8 represents a hydrogen atom or a hydroxyl group. y represents an integer of 0 to 1. z represents an integer of 0 to 1.) [3] The lubricating oil additive according to [1] or [2], wherein the polymer (A) further contains a structural unit derived from an alkyl (meth)acrylate (b) having an alkyl group having 1 to 30 carbon atoms. [4] The lubricating oil additive according to any one of [1] to [3], wherein the polymer (A) is a block copolymer or a graft copolymer. [5] The lubricating oil additive according to any one of [1] to [4], wherein the polymer (A) contains a structural unit derived from a macromonomer (M). [6] The lubricating oil additive according to [5], wherein the macromonomer (M) contains a structural unit derived from a radically polymerizable monomer (m2). [7] The lubricating oil additive according to [5], wherein the macromonomer (M) has a structure represented by the following formula (3): [ka] (In the formula, X 1 ~X p-1 each independently represents a hydrogen atom, a methyl group, or CHOH; Y 1 ~Y p each independently represents X of the radical polymerizable monomer (m2) which is a constituent unit of the macromonomer (M). 1 ~X p-1 represents a substituent of an unsaturated hydrocarbon other than the above. Z represents a terminal group, and p represents an integer of 2 to 10,000. [8] The lubricating oil additive according to any one of [1] to [7], which is a friction reducer for lubricating oil. [9] A lubricating oil composition comprising the lubricating oil additive according to any one of [1] to [8]. Effect of the Invention
[0007] According to the present invention, it is possible to provide a lubricating oil additive and a lubricating oil composition that have an excellent friction-reducing effect. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] The present invention will be described in detail below. The following embodiments are merely examples for explaining the present invention, and are not intended to limit the present invention to these embodiments. The present invention can be implemented in various forms without departing from the spirit of the present invention.
[0009] In the present invention, the following terms have the following meanings. "(Meth)acrylic" is a general term for "acrylic" and "methacrylic". "(Meth)acrylate" is a general term for "acrylate" and "methacrylate". The term "(meth)acryloyl group" is a general term for "acryloyl group" and "methacryloyl group" and is a group represented by CH2=C(R)-C(=O)- (R is a hydrogen atom or a methyl group). "Macromonomer" means a polymer having a radically polymerizable group or an addition-reactive functional group. The term "radically polymerizable monomer" means a monomer having an ethylenically unsaturated bond that is not a macromonomer.
[0010] [Lubricant additives] The lubricating oil additive of the present invention contains a polymer (A).
[0011] The polymer (A) contains a structural unit derived from a radical polymerizable monomer (a) (hereinafter also referred to as "component (a)") having a structure in which a hydroxyl group is bonded to at least two adjacent carbon atoms. The polymer (A) may further contain a structural unit derived from an alkyl (meth)acrylate (b) (hereinafter also referred to as "component (b)") having an alkyl group with 1 to 30 carbon atoms.
[0012] The content of hydroxyl groups in the polymer (A) is 0.001 to 3.70 mmol / g as the amount per 1 g of the polymer (A). If the content of hydroxyl groups is within the above range, the solubility in base oil and the friction reducing effect can be improved. The content of hydroxyl groups in the polymer (A) is preferably 0.005 to 3.00 mmol / g, more preferably 0.01 to 2.50 mmol / g, further preferably 0.05 to 2.00 mmol / g, and particularly preferably 0.10 to 1.50 mmol / g.
[0013] The component (a) is a radical polymerizable monomer having a structure in which a hydroxyl group is bonded to at least two adjacent carbon atoms. In terms of improving the friction reducing effect, the component (a) preferably contains at least one of a monomer represented by the following formula (1) and a monomer represented by the following formula (2).
[0014] [ka]
[0015] In formula (1), R 1 is a hydrogen atom or a methyl group, R 2 ~R 4 each independently represents a hydrogen atom or a hydroxyl group, and x represents an integer of 0 to 3.
[0016] [ka]
[0017] In formula (2), R 5 is a hydrogen atom or a methyl group, R 6 is an NH or oxygen atom, R 7 is an alkylene group having 1 to 5 carbon atoms or an alkylene group having 1 to 5 carbon atoms and a hydroxyl group; R 8 represents a hydrogen atom or a hydroxyl group. y represents an integer of 0 to 1. z represents an integer of 0 to 1.
[0018] R 7 Specific examples include a methylene group, an ethylene group, a propylene group, a butylene group, a pentylene group, a hydroxymethylene group, a 1-hydroxyethylene group, a 2-hydroxypropylene group, a 2-hydroxybutylene group, a 3-hydroxybutylene group, a 2-hydroxypentylene group, and a 3-hydroxypentylene group.
[0019] A specific example of the component (a) is glycerin monoacrylate (R 1 is a hydrogen atom, R 2 ~R 4 is a hydrogen atom and x is 1), glycerin monomethacrylate (a compound in which R 1 is a methyl group, R 2 ~R 4 is a hydrogen atom and x is 1), dopamine acrylamide (wherein R 5 is a hydrogen atom, R 6 NH, R 7 is an ethylene group, R 8is a hydrogen atom, y is 1, and z is 0), dopamine methacrylamide (in formula (2), R 5 is a methyl group, R 6 NH, R 7 is an ethylene group, R 8 is a hydrogen atom, y is 1, and z is 0), a compound represented by the following general formula (21), a compound represented by the following general formula (22), a compound represented by the following general formula (23), and a compound represented by the following general formula (24). The structural unit derived from the component (a) contained in the polymer (A) may be of one type or of two or more types.
[0020] [ka]
[0021] The component (b) is an alkyl (meth)acrylate in which the alkyl group has 1 to 30 carbon atoms. Specific examples of component (b) include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, n-nonyl (meth)acrylate, n-decyl (meth)acrylate, n-undecyl (meth)acrylate, and n-dodecyl (meth)acrylate. ) acrylate, n-tridecyl (meth)acrylate, n-tetradecyl (meth)acrylate, n-pentadecyl (meth)acrylate, n-cetyl (meth)acrylate, n-heptadecyl (meth)acrylate, n-stearyl (meth)acrylate, n-behenyl (meth)acrylate, and other linear alkyl (meth)acrylates; i-propyl (meth)acrylate, i-butyl (meth)acrylate, t-butyl ( (meth)acrylate, i-nonyl (meth)acrylate, i-decyl (meth)acrylate, i-undecyl (meth)acrylate, i-dodecyl (meth)acrylate, i-tridecyl (meth)acrylate, i-tetradecyl (meth)acrylate, i-pentadecyl (meth)acrylate, i-cetyl (meth)acrylate, i-heptadecyl (meth)acrylate, i-stearyl (meth)acrylate, i-octadecyl (meth)acrylate alkyl (meth)acrylates having a branched alkyl group, such as butyl acrylate, i-behenyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate; alkyl (meth)acrylates having a cyclic alkyl group, such as cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, dicyclopentanyl (meth)acrylate, isobornyl (meth)acrylate, and 4-t-butylcyclohexyl (meth)acrylate. The structural unit derived from the component (b) contained in the polymer (A) may be of one type or of two or more types.
[0022] As component (b), from the viewpoint of increasing solubility in base oil, a (meth)acrylate having a linear or branched alkyl group is preferred, a (meth)acrylate having a linear or branched alkyl group having 1 to 20 carbon atoms is more preferred, a (meth)acrylate having a linear or branched alkyl group having 2 to 18 carbon atoms is even more preferred, and a (meth)acrylate having a linear or branched alkyl group having 4 to 14 carbon atoms is particularly preferred.
[0023] The polymer (A) may contain a structural unit derived from a radically polymerizable monomer other than the components (a) and (b) (hereinafter also referred to as "component (c)"). Examples of the component (c) include styrene, α-methylstyrene, pt-butylstyrene, vinyl toluene, vinyl acetate, and (meth)acrylate compounds other than the components (a) and (b).
[0024] Examples of the (meth)acrylate compound other than the components (a) and (b) include (meth)acrylates having a hydroxyl group, such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, ethylene glycol mono(meth)acrylate, and propylene glycol mono(meth)acrylate; (meth)acrylic acid, 2-(meth)acryloyloxyethyl succinate, and maleic acid. (Meth)acrylates containing a carboxy group, such as 2-(meth)acryloyloxyethyl, 2-(meth)acryloyloxyethyl phthalate, and 2-(meth)acryloyloxyethyl hexahydrophthalate; phenyl (meth)acrylate, benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate, nonylphenoxypolyethylene glycol (meth)acrylate, and phenoxypolypropylene glycol (Meth)acrylates having an aromatic ring structure, such as phenylphenyl (meth)acrylate, phenylphenoxyethyl (meth)acrylate, phenoxybenzyl (meth)acrylate, phenylbenzyl (meth)acrylate, naphthyl (meth)acrylate, and (1-naphthyl)methyl (meth)acrylate; (meth)acrylates having a heterocyclic structure, such as tetrahydrofurfuryl (meth)acrylate, glycidyl (meth)acrylate, and (meth)acryloylmorpholine; methoxyethyl (meth)acrylate alkoxyalkyl (meth)acrylates such as ethyl acrylate, ethoxyethyl (meth)acrylate, and butoxyethyl (meth)acrylate; 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 2-(meth)acryloyloxyethyl acid phosphate, trifluoroethyl (meth)acrylate, heptadecafluorodecyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, and (meth)acrylamide. The structural unit derived from the component (c) contained in the polymer (A) may be of one type or of two or more types.
[0025] The total content of the structural units derived from component (a) and the structural units derived from component (b) in polymer (A) is preferably 70 mass% or more, more preferably 80 mass% or more, and even more preferably 90 mass% or more, based on the total mass of polymer (A).
[0026] The content of the structural unit derived from component (a) in polymer (A) is preferably 0.01 to 50 mass%, more preferably 0.05 to 40 mass%, and even more preferably 0.1 to 30 mass%, relative to the total mass of polymer (A), in terms of increasing the solubility in base oil.
[0027] The content of the structural units derived from the component (b) in the polymer (A) is preferably 50 to 99.99 mass%, more preferably 60 to 99.95 mass%, and even more preferably 70 to 99.9 mass%, relative to the total mass of the polymer (A), in terms of increasing the solubility in the base oil.
[0028] The content of the structural unit derived from the component (c) in the polymer (A) is preferably 0 to 30 mass%, more preferably 0 to 20 mass%, and even more preferably 0 to 10 mass%, based on the total mass of the polymer (A). The polymer (A) may not contain a structural unit derived from the component (c). The total amount of structural units derived from components (a) to (c) in polymer (A) does not exceed 100 mass % based on the total mass of polymer (A).
[0029] The polymer (A) may be a block copolymer or a graft copolymer in that it can have good solubility in the base oil, and is preferably a graft copolymer in that it can further improve the friction reducing effect.
[0030] In this specification, a "graft copolymer" refers to a polymer having one or more types of blocks chemically bonded as side chain polymer structures (branch polymer structures) to a main chain polymer structure (trunk polymer structure). The structures of the main chain polymer and the side chain polymer may be different or the same. The method for producing the graft copolymer is not particularly limited, but examples thereof include a method in which a macromonomer having a radically polymerizable double bond at an end is produced as a side chain polymer structure, and then radically polymerized with a monomer that becomes a constituent unit of the main chain polymer; a method in which a main chain polymer having a reactive site and a macromonomer having a reactive site are produced in advance, and then reacted with each other; and a method in which, after the production of the main chain polymer, a radical is generated on the main chain polymer using an initiator having a hydrogen abstraction ability, and then a monomer that becomes a constituent unit of the side chain polymer is reacted to produce a side chain polymer structure.
[0031] When the polymer (A) is a graft copolymer, the structural units derived from the components (a) to (c) may be contained in either the main chain polymer structure or the side chain polymer structure. The polymer (A) can have a good friction reducing effect by containing a structural unit derived from the component (a) in the side chain polymer structure or main chain polymer structure. In particular, it is preferable that the polymer (A) contains a structural unit derived from the component (a) in the main chain polymer structure in order to enhance the friction reducing effect. The polymer (A) can have good solubility in base oil by containing a structural unit derived from the component (b) in the side chain polymer structure or main chain polymer structure. In particular, it is preferable that the polymer (A) contains the component (b) in the side chain polymer structure in order to improve the solubility in base oil.
[0032] When the polymer (A) is a graft copolymer, the polymer (A) may contain a constituent unit derived from a radically polymerizable monomer (m1) (hereinafter also referred to as "(m1) component") and a constituent unit derived from a macromonomer (M) (hereinafter also referred to as "(M) component"). By copolymerizing the (m1) component and the (M) component, a graft copolymer having a main chain polymer structure containing the (m1) component as a constituent unit and a side chain polymer structure consisting of the (M) component can be obtained.
[0033] Examples of the (m1) component include the compounds listed as the (a) to (c) components. In terms of excellent radical polymerizability, the (m1) component preferably contains a (meth)acrylate compound. In terms of a good friction reducing effect, the (m1) component preferably contains the (a) component.
[0034] The (M) component is not particularly limited as long as it is a compound having a radical polymerizable group and a repeating structure, and examples thereof include compounds in which the terminals of polyisobutylene or hydrogenated polybutadiene are modified with a vinyl radical polymerizable group, and compounds containing two or more structural units derived from a radical polymerizable monomer (m2) (hereinafter also referred to as "(m2) component") and having a radical polymerizable group at the terminal. In view of the high degree of designability for solubility in base oil, it is preferable that the (M) component is a compound containing two or more structural units derived from the (m2) component and having a radical polymerizable group at the terminal.
[0035] Examples of the (m2) component include the compounds listed as the (a) to (c) components. In view of excellent radical polymerizability, it is preferable that the (m2) component contains a (meth)acrylate compound. In view of the ability to increase solubility in base oil, it is preferable that the (m2) component contains the (b) component.
[0036] From the viewpoint of radical polymerizability, the component (M) preferably has a structure represented by the following formula (3).
[0037] [ka]
[0038] In formula (3), X 1 ~X p-1 each independently represents a hydrogen atom, a methyl group, or CHOH; Y 1 ~Y p each independently represents X of the radical polymerizable monomer (m2) which is a constituent unit of the macromonomer (M). 1 ~X p-1 represents a substituent of an unsaturated hydrocarbon other than the above. Z represents a terminal group, and p represents an integer of 2 to 10,000.
[0039] X 1 ~X n-1 and Y 1 ~Y p are each independently a substituent of the unsaturated hydrocarbon of the component (m2). 1 ~Y p For example, OR 11 , halogen atom, COR 12 , COOR 13 , C.N., C.O.N. 14 R 15 , N.H.C.O.R. 16 , or R 17 R 11 ~R 17 each independently represents a hydrogen atom, an alkyl group, an aryl group, a heteroaryl group, or the like. The terminal group Z may be a hydrogen atom or a group derived from a radical polymerization initiator, as in the terminal groups of polymers obtained by known radical polymerization.
[0040] In order to improve the solubility of the polymer (A) in the base oil, the content of the structural units derived from the (M) component in the polymer (A) is preferably 1 to 50 mass%, more preferably 2 to 40 mass%, and even more preferably 3 to 30 mass%, relative to the total mass of the polymer (A).
[0041] In order to improve the solubility of the polymer (A) in the base oil, the (M) component preferably contains 50 mass % or more of structural units derived from the (b) component, based on the total mass of the (M) component, more preferably 60 mass % or more, even more preferably 70 mass % or more, and particularly preferably 80 mass % or more.
[0042] In order to improve the solubility of the polymer (A) in the base oil, the mass average molecular weight (Mw) of the (M) component measured by gel permeation chromatography (GPC) is preferably from 1,000 to 50,000, more preferably from 2,000 to 40,000, and even more preferably from 3,000 to 30,000.
[0043] In order to improve the solubility of the polymer (A) in the base oil, the number average molecular weight (Mn) of the (M) component measured by gel permeation chromatography is preferably 500 to 30,000, more preferably 1,000 to 25,000, and particularly preferably 2,000 to 20,000.
[0044] In order to improve the solubility of the polymer (A) in the base oil, the molecular weight distribution (Mw / Mn) of the (M) component measured by gel permeation chromatography (GPC) is preferably 1.0 to 10, more preferably 1.2 to 8, and even more preferably 1.5 to 5.
[0045] The component (M) may be one produced by a known method, or a commercially available product. Examples of methods for producing the component (M) include a production method using a cobalt chain transfer agent (U.S. Pat. No. 4,680,352), a method using an α-substituted unsaturated compound such as α-bromomethylstyrene as a chain transfer agent (WO 88 / 04304), a method in which a polymerizable group is chemically bonded (JP-A-60-133007 and U.S. Pat. No. 5,147,952), and a method using thermal decomposition (JP-A-11-240854). The method using a cobalt chain transfer agent is preferred in that it requires fewer production steps and uses a catalyst with a high chain transfer constant. Because the cobalt chain transfer agent has a high chain transfer constant, a macromonomer with a controlled molecular weight can be obtained by adding a small amount of the agent.
[0046] As the cobalt chain transfer agent, a known cobalt complex can be used. The amount of the cobalt chain transfer agent is preferably 0.00001 to 0.1 parts by mass, more preferably 0.00005 to 0.05 parts by mass, and particularly preferably 0.0001 to 0.02 parts by mass, relative to 100 parts by mass of the component (m2).
[0047] From the viewpoint of increasing the solubility of the polymer (A) in the base oil and increasing the friction reducing effect, the mass average molecular weight (Mw) of the polymer (A) measured by gel permeation chromatography (GPC) is preferably from 3,000 to 500,000, more preferably from 4,000 to 300,000, and even more preferably from 5,000 to 200,000.
[0048] From the viewpoint of increasing the solubility of the polymer (A) in the base oil and increasing the friction reducing effect, the number average molecular weight (Mn) of the polymer (A) measured by gel permeation chromatography (GPC) is preferably 1,000 to 200,000, more preferably 2,000 to 150,000, and even more preferably 3,000 to 100,000.
[0049] From the viewpoint of increasing the solubility of the polymer (A) in the base oil and increasing the friction reducing effect, the molecular weight distribution (Mw / Mn) of the polymer (A) measured by gel permeation chromatography (GPC) is preferably 1.0 or more and 30 or less, more preferably 1.2 or more and 20 or less, and even more preferably 1.5 or more and 10 or less.
[0050] Next, an example of the method for producing the lubricating oil additive of the present invention will be described. The lubricating oil additive of the present invention can be produced, for example, by polymerizing a monomer mixture containing component (a) and, if necessary, components (b) and (c) in a base oil by a known method. It can also be produced by polymerizing a monomer mixture containing components (m1) and (M) in a base oil by a known method. The polymerization may be carried out under known conditions, but it is preferable to use α-methylstyrene dimer as a chain transfer agent because it is particularly effective in suppressing heat generation during polymerization.
[0051] The base oil is not particularly limited, but examples thereof include API Group III base oils such as YUBASE3 manufactured by SK Lubricants, API Group III plus base oils such as YUBASE4 manufactured by SK Lubricants, and API Group IV base oils such as polyalphaolefins.
[0052] The component (M) is preferably a macromonomer obtained by polymerizing a monomer mixture containing a radically polymerizable monomer in a base oil using a cobalt chain transfer agent. Because the cobalt chain transfer agent has a high chain transfer constant, a macromonomer with a controlled molecular weight can be obtained by adding a small amount of the cobalt chain transfer agent.
[0053] The lubricating oil additive of the present invention can be used as a lubricating oil additive to be blended into engine oils, drive system oils (gear oils, transmission oils), hydraulic oils, metal processing oils, etc., which are used, for example, in mobility such as automobiles and ships, industrial machinery, robots, etc. Examples of lubricating oil additives include friction reducers intended to reduce friction, such as oiliness improvers, extreme pressure agents, antiwear agents, and friction modifiers, as well as antioxidants, viscosity index improvers, pour point depressants, detergents and dispersants, corrosion inhibitors, rust inhibitors, antifoaming agents, emulsifiers, antifungal agents, and demulsifiers. The lubricating oil additive of the present invention has an excellent friction reducing effect, and is therefore particularly preferably used as a friction reducer for lubricating oil.
[0054] [Lubricating oil composition] The lubricating oil composition of the present invention is a composition containing the lubricating oil additive of the present invention, and more specifically, is a composition in which the lubricating oil additive of the present invention is blended with a base oil.
[0055] Examples of base oils include mineral base oils refined from crude oil and synthetic oils synthesized chemically. For example, API Group III base oils such as YUBASE3 manufactured by SK Lubricants, API Group III plus base oils such as YUBASE4 manufactured by SK Lubricants, and API Group IV base oils such as polyalphaolefins can be mentioned.
[0056] The lubricating oil composition of the present invention may contain additives other than the lubricating oil additive of the present invention. Other additives include antioxidants, viscosity index improvers, pour point depressants, detergents and dispersants, corrosion inhibitors, rust inhibitors, antifoaming agents, emulsifiers, fungicides, and demulsifiers. In addition, as friction reducers other than the lubricating oil additive of the present invention, the lubricating oil may contain oiliness improvers such as long-chain fatty acid esters and fatty acid amides, antiwear agents such as phosphate esters and zinc dithiophosphates, extreme pressure agents such as organic sulfur compounds and organic halogen compounds, and friction modifiers such as molybdenum dithiocarbamate.
[0057] The lubricating oil composition of the present invention may be a grease containing a thickener. Examples of the thickener include soap-based (lithium soap, calcium soap, sodium soap, aluminum soap, etc.), inorganic (bentonite, silica gel, etc.), and organic (polyurea, polyurethane, etc.) thickeners.
[0058] The content of the lubricating oil additive of the present invention contained in the lubricating oil composition of the present invention is preferably 0.01 to 30 mass%, more preferably 0.05 to 25 mass%, and even more preferably 0.1 to 20 mass%, based on the total mass of the lubricating oil composition. When the content of the lubricating oil additive is equal to or more than the lower limit, the friction reducing effect can be increased. When the content of the lubricating oil additive is equal to or less than the upper limit, the viscosity of the lubricating oil composition can be reduced. EXAMPLES
[0059] The present invention will now be described in more detail with reference to examples and comparative examples. In the examples, "parts" refers to "parts by mass." In Tables 1 to 3, the content of the structural units derived from each monomer is shown in mass%. The content of each structural unit was calculated from the mass of each monomer relative to the total mass of the monomers used in the polymerization reaction.
[0060] [Evaluation and Measurement] The evaluations and measurements in the present examples were carried out by the following methods. <Solubility in base oil> Using a YUBASE4 solution containing 35% by mass of the (meth)acrylic polymer obtained in each Example, the solubility in base oil was evaluated according to the following criteria. ○: No precipitate ×: Precipitates present
[0061] <Molecular weight of macromonomer (M)> The molecular weight of the macromonomer (M) was measured by gel permeation chromatography (GPC) (HLC-8320, manufactured by Tosoh Corporation). After preparing a 0.2% by mass solution of the macromonomer (M) in tetrahydrofuran, 10 μL of the solution was injected into an apparatus equipped with columns manufactured by Tosoh Corporation (TSKgel SuperHZM-M (inner diameter 4.6 mm, length 15 cm), HZM-M (inner diameter 4.6 mm, length 15 cm), HZ-2000 (inner diameter 4.6 mm, length 15 cm), TSKguardcolumn SuperHZ-L (inner diameter 4.6 mm, length 3.5 cm), and measurements were performed under the conditions of a flow rate of 0.35 ml / min, eluent: tetrahydrofuran (stabilizer BHT), and column temperature: 40° C., and Mw, Mn, and molecular weight distribution (Mw / Mn) were calculated in terms of standard polystyrene.
[0062] <Molecular weight of (meth)acrylic polymer> The molecular weight of the (meth)acrylic polymer was measured by gel permeation chromatography (GPC) (HLC-8320, manufactured by Tosoh Corporation). After preparing a 0.2% by mass solution of the (meth)acrylic polymer obtained in the examples in tetrahydrofuran, 10 μL of the solution was injected into an apparatus equipped with Tosoh columns (2 TSKgel SuperHZM-H (inner diameter 6.0 mm, length 15 cm) and TSKguardcolumn SuperHZ-H (inner diameter 4.6 mm, length 3.5 cm). Measurements were performed under conditions of a flow rate of 0.5 ml / min, eluent: tetrahydrofuran (stabilizer BHT), and column temperature: 40° C., and the mass average molecular weight (Mw), number average molecular weight (Mn), and molecular weight distribution (Mw / Mn) were calculated in terms of standard polystyrene.
[0063] <Coefficient of friction> A YUBASE4 solution containing 2% by mass of the obtained (meth)acrylic polymer was prepared, and the friction coefficient was measured at 40°C using an SRV5 tester (manufactured by Optimol Instruments Pruftechnik GmbH). The measurement conditions were as follows, and the friction coefficient was evaluated 30 minutes after the start of the measurement. Test method: Ball-on-disc (ball diameter: 10mm, ball and disc material: SUJ2) Test mode: round trip (50Hz, stroke 1mm) Load capacity: 200N
[0064] [Production Example 1] (Synthesis of Co complex (cobalt chain transfer agent)) In a synthesis apparatus equipped with a stirrer, 2.00 g (8.03 mmol) of cobalt (II) acetate tetrahydrate (Wako Pure Chemical Industries, Ltd., Wako special grade), 3.86 g (16.1 mmol) of diphenylglyoxime (Tokyo Chemical Industry Co., Ltd., EP grade), and 100 mL of diethyl ether that had been deoxygenated in advance by nitrogen bubbling were placed under a nitrogen atmosphere, and the mixture was stirred at 25°C for 2 hours. Next, 20 mL of boron trifluoride diethyl ether complex (Tokyo Chemical Industry Co., Ltd., EP grade) was added and stirred for another 6 hours. The obtained product was filtered, and the solid was washed with diethyl ether and dried at 100 MPa or less at 20°C for 12 hours to obtain 5.02 g (7.93 mmol, yield 99% by mass) of a brown solid Co complex.
[0065] [Production Example 2] (Synthesis of Macromonomer M1) In a reaction vessel equipped with a stirrer, a cooling tube, and a thermometer, 58 parts of YUBASE4, 98 parts of Acryester SL (manufactured by Mitsubishi Chemical Corporation, trade name: Acryester SL, a mixture of an alkyl methacrylate with 12 carbon atoms in the alkyl group and an alkyl methacrylate with 13 carbon atoms in the alkyl group), 2 parts of methyl methacrylate (MMA), and 0.005 parts of the Co complex prepared in Production Example 1 were added, and the liquid temperature was raised to 40°C, and nitrogen was bubbled for 2 hours while stirring to remove dissolved oxygen. A mixture consisting of YUBASE4 (2 parts) and 0.1 parts of t-butylperoxy-2-ethylhexanoate (manufactured by Arkema Yoshitomi Co., Ltd., trade name: Luperox 26), a polymerization initiator, was added, and the liquid temperature was raised to 90°C. After stirring for 2.5 hours, a mixture consisting of YUBASE4 (10 parts) and Luperox 26 (0.7 parts) was added dropwise over 1 hour. After the dropwise addition, the temperature was raised to 105° C. and maintained for 1.5 hours, after which 20 parts of YUBASE4 was added and cooled to obtain a YUBASE4 solution containing 52.6% by mass of macromonomer M1. The results of GPC of the obtained macromonomer M1 are shown in Table 1.
[0066] [Production Example 3] (Synthesis of macromonomer M2) In a reaction vessel equipped with a stirrer, a cooling tube, and a thermometer, 58 parts of YUBASE4, 98 parts of Acrylate SL, 2 parts of MMA, and 0.005 parts of the Co complex prepared in Production Example 1 were added, and the liquid temperature was raised to 40°C. Nitrogen was bubbled for 2 hours while stirring to remove dissolved oxygen. A mixture consisting of YUBASE4 (2 parts) and 0.1 parts of t-amylperoxy-2-ethylhexanoate (manufactured by Arkema Yoshitomi Co., Ltd., product name: Luperox 575) as a polymerization initiator was added, the liquid temperature was raised to 90°C, and after stirring for 2.5 hours, a mixture consisting of YUBASE4 (10 parts) and Luperox 26 (0.7 parts) was added dropwise over 1 hour. After the dropwise addition, the temperature was raised to 105°C and maintained for 1.5 hours, after which 20 parts of YUBASE4 were added and cooled to obtain a YUBASE4 solution containing 52.6% by mass of macromonomer M2. The results of GPC of the obtained macromonomer M2 are shown in Table 1.
[0067] [Table 1]
[0068] [Production Example 4] (Synthesis of compound of general formula (4)) After attaching a dropping funnel to a three-necked flask containing a rotor, 2-hydroxyethyl methacrylate (95.0 g, 0.73 mol) was placed in the flask, dissolved in tetrahydrofuran (1000 mL), and triethylamine (89.2 g, 0.88 mol) was added. The mixture thus obtained was cooled to 0°C, and then methanesulfonyl chloride (101.5 g, 0.89 mol) was placed in the dropping funnel and slowly dropped into the mixture. After dropping, the mixture was reacted at 25°C for 16 hours. Next, water (800 mL) was added to the reaction mixture, and the product was extracted into the organic layer with ethyl acetate (800 mL x 3 times). The ethyl acetate solution was washed with water (800 mL) and brine (800 mL) in that order, and dehydrated with anhydrous sodium sulfate. The solvent was then removed with an evaporator to obtain methanesulfonic acid-2-ethyl methacrylate (yellow liquid, 151.0 g). In addition, the above-mentioned methanesulfonic acid-2-ethyl methacrylate1 The results of analysis by 1 H NMR were as follows: 1 H NMR (400MHz, CDCl3): δ=6.08(s, 1H), 5.57-5.54(m, 1H), 4.41-4.37(m, 2H), 4.35-4.31(m, 2H), 2.98(s, 3H), 1.88(s, 3H).
[0069] Next, gallic acid (36.0 g, 0.21 mol) and sodium hydrogen carbonate (43.0 g, 0.51 mol) were placed in a three-neck flask equipped with a rotor, and DMSO (300 mL) was added to prepare a mixture. The methanesulfonic acid-2-ethyl methacrylate (36.7 g, 0.18 mol) obtained as above was added thereto at room temperature, and the mixture was reacted at 80° C. for 16 hours. The reaction solution was returned to room temperature, water (300 mL) and 1N hydrochloric acid solution (70 mL) were added, and the product was extracted into the organic layer with ethyl acetate (400 mL x 3 times). The ethyl acetate solution was washed with water (400 mL) and brine (500 mL) in that order, and dehydrated with anhydrous sodium sulfate. The solvent was then removed with an evaporator, and the product was purified by column chromatography (packing material: silica gel, solvent: hexane / ethyl acetate mixture), and further recrystallized with a solution of ethyl acetate / n-heptane = 1 / 8 (270 mL) to obtain the compound of general formula (22) (white solid, 26.0 g).
[0070] [Example 1] 30 parts of YUBASE4 was added to a reaction vessel equipped with a stirrer, a cooling tube, and a thermometer, and dissolved oxygen was removed by bubbling nitrogen while stirring. The liquid temperature was raised to 85°C, and a mixture consisting of 25 parts of YUBASE4, 99.9 parts of lauryl acrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd., trade name: LA), 0.1 parts of glycerin monomethacrylate (manufactured by NOF Corporation, trade name: Blenmer GLM-EX), 0.1 parts of Luperox 575 as a polymerization initiator, and 0.9 parts of α-methylstyrene dimer (manufactured by NOF Corporation, trade name: Nofumer MSD) as a chain transfer agent was added dropwise over 4 hours. After maintaining at 85°C for 1 hour, a mixture of YUBASE4 (50 parts) and Luperox 575 (0.5 parts) was added dropwise over 1.5 hours. After heating to 110°C and holding for 1 hour, YUBASE4 (80.6 parts) was added and cooled to obtain a YUBASE4 solution containing 35% by mass of a (meth)acrylic polymer (polymer (A-1)). The evaluation results of the obtained polymer (A-1) are shown in Table 2.
[0071] [Example 2] 30 parts of YUBASE4 were added to a reaction vessel equipped with a stirrer, a cooling tube, and a thermometer, and dissolved oxygen was removed by bubbling nitrogen while stirring. The liquid temperature was raised to 85°C, and a mixture consisting of 25 parts of YUBASE4, 99 parts of lauryl acrylate, 1 part of glycerin monomethacrylate, 0.1 parts of Luperox 575 as a polymerization initiator, and 0.9 parts of α-methylstyrene dimer as a chain transfer agent was added dropwise over 4 hours. After holding at 85°C for 1 hour, a mixture of YUBASE4 (50 parts) and Luperox 575 (0.5 parts) was added dropwise over 1.5 hours. After raising the temperature to 110°C and holding for 1 hour, YUBASE4 (80.6 parts) was added and cooled to obtain a YUBASE4 solution containing 35% by mass of a (meth)acrylic polymer (polymer (A-2)). The evaluation results of the obtained polymer (A-2) are shown in Table 2.
[0072] [Example 3] 50 parts of YUBASE4 were added to a reaction vessel equipped with a stirrer, a cooling tube, and a thermometer, and dissolved oxygen was removed by bubbling nitrogen while stirring. The liquid temperature was raised to 85°C, and a mixture consisting of 25 parts of YUBASE4, 90 parts of lauryl acrylate, 10 parts of glycerin monomethacrylate, 0.1 parts of Luperox 575 as a polymerization initiator, and 0.9 parts of α-methylstyrene dimer as a chain transfer agent was added dropwise over 4 hours. After holding at 85°C for 1 hour, a mixture of YUBASE4 (50 parts) and Luperox 575 (0.5 parts) was added dropwise over 1.5 hours. After raising the temperature to 110°C and holding for 1 hour, YUBASE4 (60.6 parts) was added and cooled to obtain a YUBASE4 solution containing 35% by mass of a (meth)acrylic polymer (polymer (A-3)). The evaluation results of the obtained polymer (A-3) are shown in Table 2.
[0073] [Example 4] 50 parts of YUBASE4 were added to a reaction vessel equipped with a stirrer, a cooling tube, and a thermometer, and dissolved oxygen was removed by bubbling nitrogen while stirring. The liquid temperature was raised to 85°C, and a mixture consisting of 25 parts of YUBASE4, 80 parts of lauryl acrylate, 20 parts of glycerin monomethacrylate, 0.1 parts of Luperox 575 as a polymerization initiator, and 0.9 parts of α-methylstyrene dimer as a chain transfer agent was dropped over 4 hours. After holding at 85°C for 1 hour, a mixture of YUBASE4 (50 parts) and Luperox 575 (0.5 parts) was dropped over 1.5 hours. After raising the temperature to 110°C and holding for 1 hour, YUBASE4 (60.6 parts) was added and cooled to obtain a YUBASE4 solution containing 35% by mass of a (meth)acrylic polymer (polymer (A-4)). The evaluation results of the obtained polymer (A-4) are shown in Table 2.
[0074] [Example 5] 50 parts of YUBASE4 were added to a reaction vessel equipped with a stirrer, a cooling tube, and a thermometer, and dissolved oxygen was removed by bubbling nitrogen while stirring. The liquid temperature was raised to 85°C, and a mixture consisting of 25 parts of YUBASE4, 99 parts of isostearyl acrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd., product name: ISTA), 1 part of glycerin monomethacrylate, 0.1 parts of Luperox 575 as a polymerization initiator, and 0.9 parts of α-methylstyrene dimer as a chain transfer agent was dropped over 4 hours. After holding at 85°C for 1 hour, a mixture of YUBASE4 (50 parts) and Luperox 575 (0.5 parts) was dropped over 1.5 hours. After raising the temperature to 110°C and holding for 1 hour, YUBASE4 (60.6 parts) was added and cooled to obtain a YUBASE4 solution containing 35% by mass of (meth)acrylic polymer (polymer (A-5)). The evaluation results of the obtained polymer (A-5) are shown in Table 2.
[0075] [Example 6] 50 parts of YUBASE4 were added to a reaction vessel equipped with a stirrer, a cooling tube, and a thermometer, and dissolved oxygen was removed by bubbling nitrogen while stirring. The liquid temperature was raised to 85°C, and a mixture consisting of 25 parts of YUBASE4, 30 parts of lauryl acrylate, 24.5 parts of Acrylate SL, 44 parts of n-butyl acrylate, 0.5 parts of MMA, 1 part of the compound of general formula (22) synthesized in Production Example 4, 0.1 parts of Luperox 575 as a polymerization initiator, and 0.9 parts of α-methylstyrene dimer as a chain transfer agent was added dropwise over 4 hours. After maintaining at 85°C for 1 hour, a mixture of YUBASE4 (50 parts) and Luperox 575 (0.5 parts) was added dropwise over 1.5 hours. After heating to 110°C and maintaining for 1 hour, YUBASE4 (60.6 parts) was added and cooled to obtain a YUBASE4 solution containing 35% by mass of a (meth)acrylic polymer (polymer (A-6)). The evaluation results of the obtained polymer (A-6) are shown in Table 2.
[0076] [Example 7] In a reaction vessel equipped with a stirrer, a cooling tube, and a thermometer, 30 parts of YUBASE4 and 47.5 parts of the YUBASE4 solution of macromonomer M1 obtained in Production Example 2 were added, and nitrogen was bubbled while stirring to remove dissolved oxygen. The liquid temperature was raised to 85°C, and a mixture consisting of 25 parts of YUBASE4, 56 parts of n-butyl acrylate (manufactured by Mitsubishi Chemical Corporation, trade name: nBA), 18 parts of lauryl acrylate, 1 part of glycerin monomethacrylate, 0.1 parts of Luperox 575 as a polymerization initiator, and 0.4 parts of Nofumer MSD as a chain transfer agent was added dropwise over 4 hours. After maintaining at 85°C for 1 hour, a mixture of YUBASE4 (50 parts) and Luperox 575 (0.5 parts) was added dropwise over 1.5 hours. After heating to 110°C and maintaining for 1 hour, YUBASE4 (58.1 parts) was added and cooled to obtain a YUBASE4 solution containing 35% by mass of a (meth)acrylic polymer (polymer (A-7)). The evaluation results of the obtained polymer (A-7) are shown in Table 2. The monomer composition in Table 2 contains 25% by mass of macromonomer M1, and the monomers constituting macromonomer M1 are 24.5% by mass of SLMA and 0.5% by mass of MMA.
[0077] [Example 8] In a reaction vessel equipped with a stirrer, a cooling tube and a thermometer, 30 parts of YUBASE4 and 47.5 parts of the YUBASE4 solution of macromonomer M1 obtained in Production Example 2 were added, and dissolved oxygen was removed by bubbling nitrogen while stirring. The liquid temperature was raised to 85°C, and a mixture consisting of 25 parts of YUBASE4, 55 parts of n-butyl acrylate, 18 parts of lauryl acrylate, 2 parts of glycerin monomethacrylate, 0.1 parts of Luperox 575 as a polymerization initiator, and 0.6 parts of Nofumer MSD as a chain transfer agent was added dropwise over 4 hours. After maintaining at 85°C for 1 hour, a mixture of YUBASE4 (50 parts) and Luperox 575 (0.5 parts) was added dropwise over 1.5 hours. After heating to 110°C and maintaining for 1 hour, YUBASE4 (58.1 parts) was added and cooled to obtain a YUBASE4 solution containing 35% by mass of a (meth)acrylic polymer (polymer (A-8)). The evaluation results of the obtained polymer (A-8) are shown in Table 3. The monomer composition in Table 3 contains 25% by mass of macromonomer M1, and the monomers constituting macromonomer M1 are 24.5% by mass of SLMA and 0.5% by mass of MMA.
[0078] [Example 9] 27.5 parts of YUBASE4 and 47.5 parts of the YUBASE4 solution of macromonomer M1 obtained in Production Example 2 were added to a reaction vessel equipped with a stirrer, a cooling tube, and a thermometer, and dissolved oxygen was removed by bubbling nitrogen while stirring. The liquid temperature was raised to 85°C, and a mixture consisting of 25 parts of YUBASE4, 65 parts of lauryl acrylate, 10 parts of glycerin monomethacrylate, 0.1 parts of Luperox 575 as a polymerization initiator, and 0.9 parts of Nofumer MSD as a chain transfer agent was added dropwise over 4 hours. After maintaining at 85°C for 1 hour, a mixture of YUBASE4 (50 parts) and Luperox 575 (0.5 parts) was added dropwise over 1.5 hours. After heating to 110°C and maintaining for 1 hour, YUBASE4 (60.6 parts) was added and cooled to obtain a YUBASE4 solution containing 35% by mass of a (meth)acrylic polymer (polymer (A-9)). The evaluation results of the obtained polymer (A-9) are shown in Table 3. The monomer composition in Table 3 contains 25% by mass of macromonomer M1, and the monomers constituting macromonomer M1 are 24.5% by mass of SLMA and 0.5% by mass of MMA.
[0079] [Example 10] In a reaction vessel equipped with a stirrer, a cooling tube and a thermometer, 30 parts of YUBASE4 and 47.5 parts of the YUBASE4 solution of macromonomer M2 obtained in Production Example 3 were added, and dissolved oxygen was removed by bubbling nitrogen while stirring. The liquid temperature was raised to 85°C, and a mixture consisting of 25 parts of YUBASE4, 55 parts of n-butyl acrylate, 18 parts of lauryl acrylate, 2 parts of glycerin monomethacrylate, 0.1 parts of Luperox 575 as a polymerization initiator, and 0.6 parts of Nofumer MSD as a chain transfer agent was added dropwise over 4 hours. After maintaining at 85°C for 1 hour, a mixture of YUBASE4 (50 parts) and Luperox 575 (0.5 parts) was added dropwise over 1.5 hours. After heating to 110°C and maintaining for 1 hour, YUBASE4 (58.1 parts) was added and cooled to obtain a YUBASE4 solution containing 35% by mass of a (meth)acrylic polymer (polymer (A-10)). The evaluation results of the obtained polymer (A-10) are shown in Table 3. The monomer composition in Table 3 contains 25% by mass of macromonomer M2, and the monomers constituting macromonomer M2 are 24.5% by mass of SLMA and 0.5% by mass of MMA.
[0080] [Comparative Example 1] 30 parts of YUBASE4 were added to a reaction vessel equipped with a stirrer, a cooling tube, and a thermometer, and dissolved oxygen was removed by bubbling nitrogen while stirring. The liquid temperature was raised to 85°C, and a mixture consisting of 25 parts of YUBASE4, 90 parts of lauryl acrylate, 10 parts of 2-hydroxyethyl acrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd., trade name: HEA), 0.1 parts of Luperox 575 as a polymerization initiator, and 0.9 parts of α-methylstyrene dimer (manufactured by NOF Corporation, trade name: Nofumer MSD) as a chain transfer agent was dropped over 4 hours. After maintaining at 85°C for 1 hour, a mixture of YUBASE4 (50 parts) and Luperox 575 (0.5 parts) was dropped over 1.5 hours. After raising the temperature to 110°C and maintaining it for 1 hour, YUBASE4 (80.6 parts) was added and cooled to obtain a YUBASE4 solution containing 35% by mass of (meth)acrylic polymer. The evaluation results of the obtained (meth)acrylic polymer are shown in Table 3.
[0081] [Comparative Example 2] In a reaction vessel equipped with a stirrer, a cooling tube and a thermometer, 72.6 parts of YUBASE4, 44 parts of n-butyl acrylate, 30 parts of lauryl acrylate, 24.5 parts of Acryester SL, 0.5 parts of MMA, 1 part of 4HBA: 4-hydroxybutyl acrylate (manufactured by Mitsubishi Chemical Corporation, trade name: 4HBA), 0.03 parts of Perbutyl O, and 0.15 parts of Nofumer MSD were added, and dissolved oxygen was removed by bubbling nitrogen while stirring. The liquid temperature was raised to 85°C and held for 3.5 hours, after which a mixture of YUBASE4 (42 parts) and Perbutyl O (0.015 parts) was added dropwise over 2 hours. Furthermore, after holding at 85°C for 1 hour, a mixture of YUBASE4 (60 parts) and Perocta O (0.5 parts) was added dropwise over 1 hour. The temperature was then raised to 110°C and held for 1 hour, after which 11.1 parts of YUBASE4 was added and cooled to obtain a YUBASE4 solution containing 35% by mass of a (meth)acrylic copolymer. The evaluation results of the obtained (meth)acrylic polymer are shown in Table 3.
[0082] [Comparative Example 3] In a reaction vessel equipped with a stirrer, a cooling tube, and a thermometer, 50 parts of YUBASE4, 47.6 parts of the YUBASE4 solution of macromonomer M1 obtained in Production Example 2, 56 parts of n-butyl acrylate, 19 parts of lauryl acrylate, 0.03 parts of t-butylperoxy-2-ethylhexanoate (manufactured by NOF Corp., trade name: Perbutyl O) as a polymerization initiator, and 0.4 parts of Nofumer MSD as a chain transfer agent were added, and dissolved oxygen was removed by bubbling nitrogen while stirring. The liquid temperature was raised to 85°C and maintained for 3.5 hours, and then a mixture of YUBASE4 (42 parts) and Perbutyl O (0.015 parts) was added dropwise over 2 hours. Furthermore, after maintaining at 85°C for 1 hour, a mixture of YUBASE4 (30 parts) and Perocta O (0.5 parts) was added dropwise over 1 hour. After that, the temperature was raised to 110° C. and maintained for 1 hour, after which 41.1 parts of YUBASE4 was added and cooled to obtain a YUBASE4 solution containing 35% by mass of a (meth)acrylic polymer. The evaluation results of the obtained (meth)acrylic polymer are shown in Table 3.
[0083] [Comparative Example 4] 50 parts of YUBASE4 were added to a reaction vessel equipped with a stirrer, a cooling tube, and a thermometer, and dissolved oxygen was removed by bubbling nitrogen while stirring. The liquid temperature was raised to 85°C, and a mixture consisting of 25 parts of YUBASE4, 70 parts of lauryl acrylate, 30 parts of glycerin monomethacrylate, 0.1 parts of Luperox 575 as a polymerization initiator, and 0.9 parts of α-methylstyrene dimer as a chain transfer agent was added dropwise over 4 hours. After maintaining at 85°C for 1 hour, a mixture of YUBASE4 (50 parts) and Luperox 575 (0.5 parts) was added dropwise over 1.5 hours. After raising the temperature to 110°C and maintaining it for 1 hour, YUBASE4 (60.6 parts) was added and cooled. The obtained YUBASE4 solution containing 35% by mass of the (meth)acrylic polymer was rated as "x" for its solubility in base oil because precipitates were observed. In addition, the molecular weight and friction coefficient of the (meth)acrylic polymer were not evaluated.
[0084] [Table 2]
[0085] [Table 3]
[0086] The abbreviations in Tables 2 and 3 are as follows. M1: Macromonomer synthesized in Example 2 M2: Macromonomer synthesized in Example 3 GLM: Glycerin monomethacrylate (NOF Corporation, product name: Blenmar GLM-EX) Compound of formula (22): Compound synthesized in Production Example 4 LA: Lauryl acrylate (Osaka Organic Chemical Industry Co., Ltd., product name: LA) ISTA: Isostearyl acrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd., product name: ISTA) SLMA: A mixture of an alkyl methacrylate with an alkyl group having 12 carbon atoms and an alkyl methacrylate with an alkyl group having 13 carbon atoms (manufactured by Mitsubishi Chemical Corporation, product name: Acryester SL) nBA: n-Butyl acrylate (manufactured by Mitsubishi Chemical Corporation, product name: butyl acrylate) MMA: Methyl methacrylate (Mitsubishi Chemical Corporation, product name: Acryester M) HEA: 2-hydroxyethyl acrylate (Osaka Organic Chemical Industry Co., Ltd., product name: HEA) 4HBA: 4-Hydroxybutyl acrylate (Mitsubishi Chemical Corporation, product name: 4HBA)
[0087] As shown in Tables 2 and 3, the polymers (A-1) to (A-10) of Examples 1 to 10, which contain structural units derived from component (a) having a structure in which a hydroxyl group is bonded to at least two adjacent carbon atoms and have an appropriate content of hydroxyl groups, had excellent solubility in base oil, low friction coefficients in the SRV test, and excellent friction reduction effects. On the other hand, the (meth)acrylic polymers of Comparative Examples 1 to 3 did not contain a structural unit derived from the component (a), and therefore had a high friction coefficient in the SRV test and poor friction reducing effect.The (meth)acrylic polymer of Comparative Example 4 had a hydroxyl group content outside the range of 0.001 to 3.70 mmol / g, and therefore had low solubility in base oil.
Claims
1. A lubricating oil additive comprising a polymer (A) which contains a structural unit derived from a radically polymerizable monomer (a) having a structure in which a hydroxyl group is bonded to each of at least two adjacent carbon atoms, and in which the content of the hydroxyl groups is 0.001 to 3.70 mmol / g.
2. The lubricating oil additive according to claim 1, wherein the radical polymerizable monomer (a) comprises at least one of a monomer represented by the following formula (1) and a monomer represented by the following formula (2): 【Chemistry 1】 (In the formula, R 1 is a hydrogen atom or a methyl group, R 2 ~R 4 each independently represents a hydrogen atom or a hydroxyl group; and x represents an integer of 0 to 3. 【Chemistry 2】 (In the formula, R 5 is a hydrogen atom or a methyl group, R 6 is an NH or oxygen atom, R 7 is an alkylene group having 1 to 5 carbon atoms or an alkylene group having 1 to 5 carbon atoms and a hydroxyl group; R 8 represents a hydrogen atom or a hydroxyl group. y represents an integer of 0 to 1. z represents an integer of 0 to 1.)
3. The lubricating oil additive according to claim 1, wherein the polymer (A) further comprises a structural unit derived from an alkyl (meth)acrylate (b) having an alkyl group having 1 to 30 carbon atoms.
4. The lubricating oil additive according to claim 1, wherein the polymer (A) is a block copolymer or a graft copolymer.
5. The lubricating oil additive according to claim 1 , wherein the polymer (A) contains a structural unit derived from a macromonomer (M).
6. The lubricating oil additive according to claim 5 , wherein the macromonomer (M) contains a structural unit derived from a radically polymerizable monomer (m2).
7. The lubricating oil additive according to claim 5 , wherein the macromonomer (M) has a structure represented by the following formula (3): 【Chemistry 3】 (In the formula, X 1 ~X p-1 are each independently a hydrogen atom, a methyl group, or CH 2 OH, Y 1 ~Y p each independently represents X of the radical polymerizable monomer (m2) which is a structural unit of the macromonomer (M). 1 ~X p-1 Z represents a terminal group, and p represents an integer of 2 to 10,000.
8. 2. The lubricating oil additive of claim 1, which is a friction reducer for lubricating oil.
9. A lubricating oil composition comprising the lubricating oil additive according to any one of claims 1 to 8.
Citation Information
Patent Citations
Friction and wear reducing agent for lubricating oil and lubricating oil composition containing the same
JP2013124266A